Composite lithium supplementing material and preparation method and application thereof
By using composite lithium supplementary materials in lithium-ion batteries, and using functional material filling to improve conductive performance and structural stability, the problem of limited stability and performance improvement of existing lithium supplementary materials in lithium-ion batteries is solved, and lithium-ion is realized Highly efficient lithium replenishment and long life of the battery.
Patent Information
- Application Number
- CN202411393685.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing lithium supplementary materials have problems such as poor structural stability and poor conductivity in lithium-ion batteries, resulting in shortening of the life of lithium-ion batteries and limited performance improvement.
Using composite lithium supplement material, by filling functional materials such as ion conductor materials, electronic conductor materials and catalysts between the two lithium supplement materials, ion conductor properties and electron conductor properties are improved, and structural support is provided to enhance delitting ability and stability. .
It improves the delitting ability and structural stability of lithium supplement materials, extends the circulation performance and life of lithium-ion batteries, and enhances the energy density and efficient lithium supplement performance of the battery.
Smart Images

Figure CN119297284A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery materials, and in particular relates to a composite lithium supplement material and a preparation method and application thereof. Background Art
[0002] During the first charge and discharge of liquid lithium-ion batteries, the lithium ions released from the positive electrode material react with the electrolyte to form a solid electrolyte interface (SEI) on the surface of the negative electrode material. This process will irreversibly consume the lithium source in the positive electrode material, reducing the coulomb efficiency in the first cycle, and will also continue to consume the active lithium in the positive electrode during the charge and discharge cycle of the lithium battery, resulting in a shortened life of the lithium-ion battery. In order to solve the problem of irreversible consumption of lithium ions during the formation of the SEI film, lithium replenishment materials are used to replenish lithium-ion batteries. The lithium replenishment materials decompose and release active lithium during the battery charging process to reduce lithium loss during the cycle.
[0003] However, lithium-supplementing materials have problems such as poor structural stability and poor conductivity, which are not conducive to the promotion and application of lithium-supplementing materials and limit the improvement of lithium-ion battery performance. Summary of the invention
[0004] The purpose of the present application is to provide a composite lithium supplement material and a preparation method and application thereof, aiming to solve the problem that lithium supplement materials have poor lithium supplement effects.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a composite lithium supplement material, comprising:
[0007] At least two lithium supplementing materials are provided, and a functional material is filled between two adjacent lithium supplementing materials, and the functional material includes at least one of an ion conductor material, an electronic conductor material and a catalyst.
[0008] In a second aspect, the present application provides a method for preparing a composite lithium supplement material, comprising the following steps:
[0009] Providing a first lithium supplement material and a second lithium supplement material;
[0010] At least one of the first lithium supplement material and the second lithium supplement filling ion conductor material, electronic conductor material and catalyst forms a functional material to obtain a composite lithium supplement material.
[0011] In a third aspect, the present application provides a positive electrode material, including the composite lithium-replenishing material in the first aspect and / or the composite lithium-replenishing material prepared by the preparation method of the composite lithium-replenishing material provided in the second aspect.
[0012] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate comprises the positive electrode material in the third aspect.
[0013] The composite lithium-supplementing material provided in the first aspect of the present application comprises at least two lithium-supplementing materials and a functional material, and the functional material is filled between two adjacent lithium-supplementing materials, thereby enabling both lithium-supplementing materials to achieve good contact with the functional material, which is more conducive to the functional material to exert its effect, including improving the ion conductivity or electron conductivity of the lithium-supplementing material, and reducing the decomposition voltage of the lithium-supplementing material, thereby enabling the lithium-supplementing material to have a high lithium-removal ability; in addition, the functional material can provide support for the two lithium-supplementing materials, thereby effectively improving the structural stability of the lithium-supplementing material, and thus, during the charge and discharge process, it is not easy for the electrode to produce pits or gaps due to lithium-removal decomposition, which has a positive impact on the overall structural stability of the electrode.
[0014] The preparation method of the composite lithium supplement material provided in the second aspect of the present application effectively prepares the composite lithium supplement material having the properties of the composite lithium supplement material of the present application by filling the functional materials in the two lithium supplement materials. In addition, the preparation method of the composite lithium supplement material of the present application is conducive to obtaining a composite lithium supplement material with a stable structure, so that the lithium supplement performance can be fully exerted, and the composite lithium supplement material is endowed with excellent lithium removal ability, so as to achieve efficient lithium supplementation of the battery, which is conducive to wide application.
[0015] The positive electrode material provided in the third aspect of the present application contains the composite lithium replenishing material provided in the present application, and the composite lithium replenishing material has good stability and high lithium replenishing capacity. It can provide active lithium ions that compensate for the consumption of the battery due to the formation of the SEI film during the first charge, thereby achieving efficient lithium replenishment, thereby effectively maintaining the gram capacity of the positive electrode material and improving the capacity retention rate of the positive electrode material.
[0016] The secondary battery provided in the fourth aspect of the present application contains the positive electrode material of the present application. Therefore, the secondary battery of the present application has high first efficiency and energy density, and has relatively high and stable cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 is a schematic diagram of the structure of the composite lithium supplement material provided in the embodiment of the present application;
[0019] Figure 2It is a schematic diagram of a step in the method for preparing a composite lithium supplement material provided in an embodiment of the present application;
[0020] Figure 3 It is a schematic diagram of another step in the method for preparing the composite lithium supplement material provided in the embodiment of the present application.
[0021] Among them, the reference numerals in the figure are:
[0022] 100. composite lithium supplement material, 200. first glass substrate, 300. intermediate;
[0023] 10. functional material layer, 20. first lithium supplement layer, 30. second lithium supplement layer, 40. ion conduction layer, 50. electron conduction layer;
[0024] 11. Void layer;
[0025] 21, I precursor, 22, II precursor. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0027] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0028] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0029] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0030] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0031] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0032] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0033] In the description of the embodiments of the present application, SEI (solid electrolyte interface) membrane refers to a solid electrolyte phase interface membrane having the characteristics of a solid electrolyte, that is, a membrane formed by a passivation layer covering the surface of the electrode material when the electrode material and the electrolyte react at the solid-liquid interface during the first charge and discharge process of a liquid lithium-ion battery.
[0034] The first aspect of the embodiment of the present application provides a composite lithium supplement material, including:
[0035] At least two lithium supplementing materials are provided, and a functional material is filled between two adjacent lithium supplementing materials, and the functional material includes at least one of an ion conductor material, an electronic conductor material and a catalyst.
[0036] In the technical solution of the present application, both lithium supplement materials can be used for lithium supplement, so that the composite lithium supplement material can provide more lithium ions to offset the irreversible lithium loss caused by the formation of SEI film, thereby improving the total capacity and energy density of the battery. Functional materials are filled between the two lithium supplement materials, so that the lithium supplement materials have a larger contact area with the functional materials, which is more conducive to the function of the functional materials, including improving the ion conductivity or electron conductivity of the lithium supplement material, and reducing the decomposition voltage of the lithium supplement material, thereby making the lithium supplement material have a better lithium removal effect.
[0037] In one embodiment, the functional material includes an ion conductor material, which has good ion conductivity. It can not only serve as a transmission channel for lithium ions, providing a continuous and unobstructed transmission path for lithium ions, but also transfer its good conductivity to the lithium supplement material, thereby improving the overall lithium ion transmission capacity of the lithium supplement material. In this way, lithium ions can be embedded in and out of the lithium supplement material more quickly, and exert good lithium supplement performance. In another embodiment, the functional material includes an electronic conductor material, which has excellent electronic conductivity and can improve the electronic transmission capacity of the lithium supplement material in contact with it, thereby making the electron transfer in the charging and discharging process more rapid and efficient, thereby promoting the embedding and extraction of lithium ions, thereby effectively exerting the lithium supplement capacity of the lithium supplement material. In another embodiment, the functional material includes a catalyst, and at this time the catalyst has a large contact area with the lithium supplement material, so that the reaction activation energy of the lithium supplement material for delithiation can be effectively reduced, its reaction activity can be improved, the decomposition voltage of the lithium supplement material can be reduced, and the capacity utilization rate of the lithium supplement material can be effectively improved.
[0038] The presence of functional materials makes it difficult for lithium-supplementing materials to agglomerate, which is conducive to the role of lithium-supplementing materials. At the same time, the functional materials also provide physical support for the two lithium-supplementing materials, which helps to withstand the stress during the charging and discharging process and maintain the integrity of the structure. In this way, the distribution of lithium-supplementing materials effectively improves the structural stability of the two lithium-supplementing materials, and it is not easy to produce pits or gaps in the pole piece due to decomposition due to lithium removal during the charging and discharging process, which has a positive impact on the overall structural stability of the pole piece.
[0039] The two lithium-supplementing materials include a first lithium-supplementing material and a second lithium-supplementing material in a specific distribution mode, so that the lithium-supplementing material and the functional material have a good contact effect, thereby giving full play to the role of the functional material and achieving efficient lithium supplementation. In one embodiment, the first lithium-supplementing material and the second lithium-supplementing material are the same, thereby improving the lithium removal ability of the lithium-supplementing material and giving full play to the lithium supplementation ability of the lithium-supplementing material. In another embodiment, the first lithium-supplementing material and the second lithium-supplementing material are different, so that the two lithium-supplementing materials play a synergistic role and obtain a composite lithium-supplementing material with excellent lithium supplementation effect.
[0040] In some embodiments, the first lithium supplement material and the second lithium supplement material are different. Exemplarily, the first lithium supplement material can be one of a binary lithium supplement agent, a ternary lithium supplement agent and an organic lithium salt, and the second lithium supplement material can be another of a binary lithium supplement agent, a ternary lithium supplement agent and an organic lithium salt. Exemplarily, the first lithium supplement material can be one of a ternary lithium supplement agent, and the second lithium supplement material can be another of a ternary lithium supplement agent.
[0041] Exemplarily, the chemical formula of the ternary lithium supplement is Li a M b O c, wherein M is at least one element selected from Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1≤a≤8, 0<b, 0<c<7. In a specific embodiment, the ternary lithium supplement may be Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, LiFeO2, Li2CuO2, Li2CoO2, Li6CoO4, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4、Li2Ni d Cu (1-d) At least one of O2 (0<d<1), etc.
[0042] Exemplarily, the chemical formula of the binary lithium supplement is Li k M m , wherein M is at least one element selected from S, P, N, F, B, O, Se, and Te, 1≤k≤5, and 0≤m. Binary lithium supplements include but are not limited to at least one selected from Li3N, Li2S, LiF, Li3P, Li2Se, and Li2O.
[0043] Exemplary organic lithium salts include but are not limited to one or more of Li2C3O3, Li2C4O4, Li2C6O6, Li2C3O5, Li2C2O4 and Li2C4O6. It is understood that lithium-rich materials such as lithium oxalate have a higher theoretical capacity (>525 mAhg -1 ) and good air stability, it is considered to be an attractive lithium supplement material.
[0044] In some embodiments of the present application, the organic lithium salt also includes other lithium-supplementing materials with higher decomposition voltages, mainly including lithium-supplementing materials with a delithiation potential above 4V, such as Li2O (delithiation potential 4.5V), Li2O2 (delithiation potential 4.3V), LiOH (delithiation potential 4.8V), Li4SiO4 (delithiation potential 4.5V), Li3PO4 (delithiation potential exceeding 4V), Li2CO3 (delithiation potential 4.7V), and Li5FeO4 (delithiation potential 4V).
[0045] The above-mentioned organic lithium salts all have high capacity, but these organic lithium salts require a high charging voltage for delithiation, and there is a technical problem of high platform voltage. These organic lithium salts with higher decomposition voltages are also difficult to compound with conventional positive electrode materials (such as lithium iron phosphate, whose delithiation potential is about 3.5V), which limits the wide application of lithium supplement materials. Therefore, the present application effectively promotes the decomposition of organic lithium salts and reduces the decomposition voltage by utilizing the catalytic effect of functional materials such as catalysts.
[0046] Lithium supplement materials have similarities and certain differences in terms of conductivity, gas production performance, volume expansion and contraction, theoretical capacity, residual alkali value, thermal stability, etc. Therefore, the embodiments of the present application can select appropriate first lithium supplement materials and second lithium supplement materials to achieve complementary advantages or synergistic performance in terms of performance, and achieve enhanced conductivity, increased actual capacity, or reduced gas production, volume expansion and other performance improvements. For example, the first lithium supplement material is one of the ternary lithium supplement agents, which has a higher capacity, and the second lithium supplement material is another of the ternary lithium supplement agents, which has a lower residual alkali value. The cooperation of the two can not only improve the lithium supplement capacity of the composite lithium supplement material, but also reduce the residual alkali value of the composite lithium supplement material, so as to improve the stability and safety performance of the composite lithium supplement material.
[0047] In some embodiments, the ion conductor material includes at least one of a metal ion conductor, a ceramic ion conductor, and a solid electrolyte.
[0048] These ion conductor materials have good ionic conductivity, can provide more transmission channels for lithium ions, promote the rapid and effective migration of lithium ions, thereby facilitating the deintercalation of lithium ions and effectively improving the capacity utilization of the composite lithium supplement material.
[0049] As an example, the solid electrolyte includes, but is not limited to, at least one of lithium aluminum titanium phosphate (LATP), lanthanum chloride (LaCl 3 ), and lithium lanthanum titanate (LLTO).
[0050] In some embodiments, the electronic conductor material includes at least one of a carbon material, a metal single atom, an alloy, and a conductive polymer material.
[0051] These electronic conductor materials have high electronic conductivity and can effectively improve the conductivity of the lithium supplement material, so that electrons can be transferred at a faster speed, thereby promoting the insertion and extraction of lithium ions, so that the lithium supplement material can fully exert its lithium supplement capacity.
[0052] As an example, the carbon material includes but is not limited to at least one of graphene, carbon nanotubes, activated carbon, carbon fiber, and carbon black.
[0053] As an example, the metal single atom includes but is not limited to at least one of aluminum, silver, iron, cobalt, nickel, and copper.
[0054] As an example, the conductive polymer material includes but is not limited to at least one of polyaniline, polypyrrole, polythiophene, and polyacetylene.
[0055] In some embodiments, the catalyst includes a transition metal compound. Exemplarily, the transition metal compound includes at least one of a transition metal oxide, a transition metal carbide, a transition metal sulfide, and a transition metal phosphide.
[0056] These catalysts have good catalytic effects and can effectively reduce the decomposition voltage of the lithium supplement material, so that the composite lithium supplement material can provide sufficient lithium ions, so that the composite lithium supplement material has a high capacity utilization rate.
[0057] In some embodiments, the corresponding transition metal in the transition metal compound includes at least one of nickel (Ni), cobalt (Co), manganese (Mn), and iron (Fe).
[0058] In some embodiments, the two lithium supplementing materials and the functional material form a stacked structure, and the functional material forms a functional material layer between the two lithium supplementing materials.
[0059] The stacked existence means that the two lithium-supplementing materials are respectively distributed on two surfaces of the functional material layer that are relatively arranged, such as the first lithium-supplementing material is distributed on one surface of the functional material layer, and the second lithium-supplementing material is distributed on the other surface of the functional material layer. This makes it difficult for the lithium-supplementing materials to agglomerate, which is conducive to the role of the lithium-supplementing materials. At the same time, the functional material layer also provides physical support for the first lithium-supplementing material and the second lithium-supplementing material, which helps to withstand the stress during the charging and discharging process and maintain the integrity of the structure. In this way, the distribution of lithium-supplementing materials effectively improves the structural stability of the first lithium-supplementing material and the second lithium-supplementing material, and it is not easy to produce pits or gaps in the pole piece due to decomposition due to lithium removal during the charging and discharging process, which has a positive impact on the overall structural stability of the pole piece. Therefore, the composite lithium-supplementing material with a lamellar structure is easier to decompose during the charging and discharging process of the battery, is not easy to remain, and is not easy to have an adverse effect on the pole piece.
[0060] In some embodiments, the thickness of the functional material layer is 20 nm-800 nm. Exemplarily, the thickness of the functional material layer can be 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, etc., which are typical but non-limiting values.
[0061] Controlling the thickness of the functional material layer within the above range can effectively shorten the transmission distance of lithium ions in the functional material layer and reduce the transmission resistance, so that lithium ions can quickly reach the lithium replenishing material or escape from the lithium replenishing material, thereby effectively improving the lithium ion transmission rate and lithium replenishing effect.
[0062] In some embodiments, the functional material layer includes an atomic deposition layer obtained by depositing at least one of an ion conductor material, an electron conductor material, and a catalyst using an atomic layer deposition technique.
[0063] The atomic layer deposition technology can obtain an atomic deposition layer with suitable thickness, uniformity and high surface consistency. In particular, the atomic deposition layer is located between the two lithium supplement materials, so that the atomic deposition layer and the two lithium supplement materials have excellent contact effects, thereby effectively improving the role of the atomic deposition layer.
[0064] In some embodiments, the two lithium supplementing materials form secondary particles, and the gaps between the secondary particles are filled with the functional material.
[0065] Secondary particles are formed by stacking and agglomerating multiple primary particles. In the present application, secondary particles are formed by stacking multiple primary particles of lithium supplement materials. Since the size and shape of the lithium supplement material particles are slightly different, the formation process of secondary particles is often uneven, so that gaps will be generated between the secondary particles.
[0066] It can be understood that, unlike the aforementioned stacked composite lithium supplement material, in these embodiments, the composite lithium supplement material is formed by the aggregation of multiple primary particles of lithium supplement materials and functional materials. Specifically, gaps are formed between adjacent primary particles of lithium supplement materials, and the gaps in the secondary particles are filled with functional materials, so that the particles of the lithium supplement material are more densely stacked, thereby forming a more stable structure of the two lithium supplement materials and maintaining the integrity of the structure; in addition, the filling of functional materials increases the contact area between the lithium supplement material and the functional material, which is more conducive to the function of the functional material.
[0067] In some embodiments, the two lithium-replenishing materials include a first lithium-replenishing material and a second lithium-replenishing material, the functional material layer includes a first surface and a second surface oppositely arranged along the thickness direction, the first lithium-replenishing material is attached to the first surface of the functional material layer to form a first lithium-replenishing layer, and the second lithium-replenishing material is attached to the second surface of the functional material layer to form a second lithium-replenishing layer.
[0068] See also Figure 1 The composite lithium replenishing material 100 includes a first lithium replenishing layer 20 , a functional material layer 10 and a second lithium replenishing layer 30 which are stacked one on another. The functional material layer 10 is disposed between the first lithium replenishing layer 20 and the second lithium replenishing layer 30 .
[0069] The first lithium supplement material is attached to the surface of the functional material layer to form the first lithium supplement layer, that is, the first lithium supplement layer and the functional material layer form a stacked sheet structure, and the second lithium supplement material is attached to the surface of the functional material layer to form the second lithium supplement layer, that is, the second lithium supplement layer is stacked on the surface of the functional material layer. On the one hand, it means that the functional material layer can provide more active sites to accommodate more first lithium supplement materials and second lithium supplement materials attached to the surface of the functional material layer in a relatively uniform form, thereby providing a higher lithium supplement capacity; on the other hand, the sheet structure can disperse the stress in the lithium supplement process, reduce the damage of the local structure, and better withstand the changes in the charging and discharging process, thereby improving the structural stability and cycle life of the composite lithium supplement material. In addition, the sheet structure can provide an orderly transmission path for lithium ions, which is conducive to the rapid and orderly migration of lithium ions between the functional material layer and the first lithium supplement layer, making the insertion and extraction of lithium ions smoother, thereby improving the lithium supplement effect of the lithium supplement material.
[0070] The sheet structure can form an orderly transmission channel, so that lithium ions can migrate quickly and evenly between the first lithium replenishment layer, the functional material layer and the second lithium replenishment layer, which makes the migration process of lithium ions easier to occur, which is conducive to the first lithium replenishment material and the second lithium replenishment material to achieve efficient lithium replenishment. In addition, the sheet structure enhances the close contact between the first lithium replenishment layer and the functional material layer and between the functional material layer and the second lithium replenishment layer, which is conducive to reducing the interface resistance and significantly improving the transmission rate of electrons and ions at the interface. In this way, the composite lithium replenishment material exhibits an excellent lithium replenishment effect.
[0071] In some embodiments, the thickness of the first lithium supplement layer is 100 nm-3000 nm. For example, the thickness of the first lithium supplement layer can be 100 nm, 200 nm, 400 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, etc., which are typical but non-limiting values.
[0072] Controlling the thickness of the first lithium replenishing layer within the above range not only allows lithium ions to have a shorter transmission path, thereby helping to improve the transmission rate of lithium ions, but also the first lithium replenishing material is relatively evenly dispersed and has a larger contact area with the functional material layer, making it easier to decompose the first lithium replenishing material, thereby achieving efficient lithium replenishment.
[0073] In some embodiments, the thickness of the second lithium supplement layer is 100 nm-3000 nm. For example, the thickness of the second lithium supplement layer can be 100 nm, 200 nm, 400 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, etc., which are typical but non-limiting values.
[0074] Controlling the thickness of the second lithium replenishing layer within the above range not only allows lithium ions to have a shorter transmission path, thereby helping to increase the transmission rate of lithium ions, but also the second lithium replenishing material is relatively evenly dispersed and has a larger contact area with the functional material layer, making it easier to decompose the second lithium replenishing material, thereby achieving efficient lithium replenishment.
[0075] In some embodiments, the two lithium-replenishing materials and the functional material layer form a lithium-replenishing unit, the composite lithium-replenishing material includes a lithium-replenishing matrix, and the lithium-replenishing matrix includes at least one lithium-replenishing unit.
[0076] Two lithium-supplementing materials and the functional material layer form a lithium-supplementing unit, that is, the first lithium-supplementing material, the second lithium-supplementing material and the functional material layer form a lithium-supplementing unit. In one embodiment, the lithium-supplementing matrix includes only one lithium-supplementing unit. In another embodiment, the lithium-supplementing matrix includes two or more lithium-supplementing units. In this case, the lithium-supplementing materials in the multiple lithium-supplementing units may be the same or different. As an example, the lithium-supplementing matrix includes a first lithium-supplementing unit and a second lithium-supplementing unit, the first lithium-supplementing unit includes a first lithium-supplementing material and a second lithium-supplementing material, and the second lithium-supplementing unit includes a third lithium-supplementing material and a fourth lithium-supplementing material, wherein the first lithium-supplementing material, the second lithium-supplementing material, the third lithium-supplementing material and the fourth lithium-supplementing material are all different.
[0077] If the lithium-supplementing matrix includes a plurality of lithium-supplementing units, the plurality of lithium-supplementing units are stacked to form a lamellar structure, so that an orderly transmission channel is formed between the lithium-supplementing units, so that lithium ions can migrate between the lithium-supplementing matrices at a faster speed. In addition, the lamellar structure enhances the close contact between the lithium-supplementing matrices, thereby facilitating the reduction of the interface resistance, so that the transmission rate of electrons and ions at the interface is significantly improved, so that the composite lithium-supplementing material exhibits an excellent lithium-supplementing effect.
[0078] In some embodiments, the lithium-supplemented matrix includes a first surface and a second surface disposed opposite to each other along a thickness direction;
[0079] The composite lithium supplement material further comprises ion conductor nanosheets, and the ion conductor nanosheets are combined on the first surface of the lithium supplement matrix.
[0080] Ion conductor nanosheets have excellent ionic conductivity and can provide more transmission channels for lithium ions, which is conducive to improving the ability of lithium-supplementing materials to transmit lithium ions outward, so that the lithium-supplementing capacity of lithium-supplementing materials can be effectively utilized. In addition, ion conductor nanosheets also have a supporting role, effectively relieving the stress of lithium-supplementing materials during the charging and discharging process, so that the structural stability of composite lithium-supplementing materials is effectively improved.
[0081] In some embodiments, the thickness of the ion conductor nanosheet is 50 nm-800 nm. For example, the thickness of the ion conductor nanosheet can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, etc., which are typical but non-limiting values.
[0082] The thickness of the ion conductor nanosheet is controlled within the above range, so that the lithium ions have a suitable transmission distance, thereby improving the migration rate of the lithium ions. In addition, within the above range, the ion conductor nanosheet is in closer contact with the lithium supplement matrix, forming a uniform and orderly lithium ion transmission channel, so as to effectively improve the lithium supplement performance.
[0083] In some embodiments, at least one ion conductor nanosheet is stacked on a surface of the lithium-supplemented matrix away from the functional material layer to form an ion conducting layer.
[0084] One or more ion conductor nanosheets form an ion conductive layer, which means that the lithium supplement matrix and the ion conductive layer form a stacked sheet structure, thereby forming a uniform and orderly lithium ion transmission channel, promoting the rapid migration of lithium ions, and effectively improving the lithium supplement effect. In addition, the sheet structure can effectively disperse the stress and strain of the lithium supplement material during the charging and discharging process, so that the structural stability of the composite lithium supplement material is significantly improved.
[0085] See also Figure 1 The composite lithium supplement material 100 includes a lithium supplement matrix and an ion conductive layer 40. The lithium supplement matrix includes a lithium supplement unit. Specifically, the lithium supplement matrix includes a first lithium supplement layer 20, a functional material layer 10 and a second lithium supplement layer 30 stacked in layers. The ion conductive layer 40 and the lithium supplement matrix form a stacked form.
[0086] In some embodiments, the lithium-supplemented matrix includes a first surface and a second surface disposed opposite to each other along a thickness direction;
[0087] The composite lithium supplement material further comprises electronic conductor nanosheets, and the electronic conductor nanosheets are combined on the second surface of the lithium supplement matrix.
[0088] The electronic conductor nanosheets have good electronic conductivity, which can improve the electron transport capacity of the lithium-supplementing material, allowing electrons to migrate quickly in the composite lithium-supplementing material, which is conducive to accelerating the insertion and extraction of lithium ions, thereby effectively improving the capacity utilization of the lithium-supplementing material.
[0089] In some embodiments, the thickness of the electron conductor nanosheet is 50 nm-800 nm. For example, the thickness of the electron conductor nanosheet can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, etc., which are typical but non-limiting values.
[0090] Controlling the thickness of the electronic conductor nanosheet within the above range not only allows the electronic conductor nanosheet to form a more uniform and close interface contact with the lithium-supplementing material, which is beneficial to reducing the interface resistance and interface polarization, but also allows electrons to have a shorter transmission path, allowing electrons to be transmitted at a faster speed in the lithium-supplementing material, which helps to improve the lithium delithiation efficiency of the lithium-supplementing material.
[0091] In some embodiments, at least one electronic conductor nanosheet is stacked on a surface of the lithium-supplemented matrix away from the functional material layer to form an electronic conduction layer.
[0092] See also Figure 1 The composite lithium supplement material 100 includes a lithium supplement matrix and an electronic conductive layer 50. The lithium supplement matrix includes a lithium supplement unit. Specifically, the lithium supplement matrix includes a first lithium supplement layer 20, a functional material layer 10 and a second lithium supplement layer 30 stacked in layers. The lithium supplement matrix and the electronic conductive layer 50 form a stacked form.
[0093] One or more electron conductor nanosheets form an electron conduction layer and are stacked on the surface of the lithium replenishment matrix, so that the lithium replenishment matrix and the electron conduction layer form a stacked sheet structure, thereby constructing an effective electron transport network, which helps electrons reach the active sites of lithium ions at a faster speed, thereby improving the lithium replenishment rate and lithium replenishment effect.
[0094] In some embodiments, the ion conductor nanosheets include at least one of a metal ion conductor, a ceramic ion conductor, and a solid electrolyte.
[0095] These ion conductor nanosheets have high ionic conductivity and can provide a continuous and low-resistance transmission channel for lithium ions, which is beneficial for the rapid migration of lithium ions in the lithium replenishment material and improves the lithium replenishment efficiency.
[0096] In some embodiments, the electron conductor nanosheets include at least one of carbon materials, metal single atoms, alloys, and conductive polymer materials.
[0097] These electronic conductor nanosheets have high conductivity, provide an excellent conductive environment for lithium replenishment materials, increase the ability of lithium ions to be transmitted outward, and help lithium replenishment materials to remove lithium, thereby achieving efficient lithium replenishment.
[0098] In some embodiments, the composite lithium supplement material includes an ion conducting layer, a lithium supplement matrix and an electron conducting layer stacked from bottom to top, or the composite lithium supplement material includes an electron conducting layer, a lithium supplement matrix and an ion conducting layer stacked from bottom to top.
[0099] See also Figure 1The composite lithium supplement material 100 includes an ion conductive layer 40, a lithium supplement matrix and an electronic conductive layer 50 stacked from bottom to top, the lithium supplement matrix includes a lithium supplement unit, and the lithium supplement unit includes a first lithium supplement layer 20, a functional material layer 10, and a second lithium supplement layer 30 stacked. Thus, the composite lithium supplement material 100 includes an ion conductive layer 40, a first lithium supplement layer 20, a functional material layer 10, a second lithium supplement layer 30 and an electronic conductive layer 50 stacked from bottom to top, wherein the functional material layer 10 is arranged between the first lithium supplement layer 20 and the second lithium supplement layer 30, the first lithium supplement layer 20 is arranged between the ion conductive layer 40 and the functional material layer 10, and the second lithium supplement layer 30 is arranged between the electronic conductive layer 50 and the functional material layer 10.
[0100] The composite lithium-replenishing material has a lamellar structure, which can effectively alleviate the volume change of the lithium-replenishing material during the charging and discharging process, can better maintain the structural integrity, enhance the structural stability of the lithium-replenishing material, and extend its service life.
[0101] Since the composite lithium supplement material is a sacrificial lithium salt, it releases lithium ions as much as possible during the charge and discharge process to replenish the irreversible lithium ions consumed by the formation of the SEI film at the negative electrode. Therefore, after the composite lithium supplement material with a layered structure undergoes delithiation and decomposition, the electrode is not prone to pits or gaps due to the presence of supporting layers such as functional material layers, ion conductive layers or electron conductive layers.
[0102] A second aspect of the present application provides a method for preparing a composite lithium supplement material, comprising the following steps:
[0103] Step S10, providing a first lithium supplement material and a second lithium supplement material;
[0104] Step S20, forming a functional material by filling at least one of the first lithium supplementing material and the second lithium supplementing material with an ion conductor material, an electronic conductor material and a catalyst to obtain a composite lithium supplementing material.
[0105] The preparation method of the composite lithium supplement material provided in the second aspect of the embodiment of the present application effectively prepares the composite lithium supplement material having the performance as described above by filling the functional materials in the two lithium supplement materials. In addition, the preparation method of the composite lithium supplement material of the present application is conducive to obtaining a composite lithium supplement material with a stable structure, so that the lithium supplement performance can be fully exerted, and the composite lithium supplement material is endowed with excellent lithium removal ability, so as to achieve efficient lithium supplementation of the battery, which is conducive to wide application.
[0106] In some embodiments, in step S10, the first lithium supplementing material and the second lithium supplementing material can be prepared by a template method.
[0107] Specifically, the preparation method of the first lithium supplement material includes the following steps:
[0108] Step S11, placing a precursor raw material of a first lithium supplement material on the surface of a glass substrate, sintering the precursor raw material to form the first lithium supplement material on the surface of the glass substrate, and separating the precursor raw material from the glass substrate to obtain the first lithium supplement material.
[0109] The specific conditions of the sintering treatment are set according to the specific components of the first lithium supplementing material.
[0110] As an example, the specific process of forming Li6CoO4 material on the surface of a glass substrate is as follows:
[0111] After degassing and mixing the excess LiOH and CoO powder, place them on the surface of the glass substrate;
[0112] The material was kept at 450-480°C for 2 hours, then heated to 750°C and sintered for 6 hours to form Li6CoO4 material, which was then treated with 0.05 mol / L sodium hydroxide solution and separated from the glass substrate to obtain the first lithium supplement material.
[0113] At 450°C-480°C, LiOH melts and becomes liquid, thereby being evenly distributed on the surface of the ion conductor nanosheet. At this time, a lithium replenishment layer of appropriate thickness can be formed by controlling the mass of the first lithium replenishment material precursor.
[0114] The preparation process of the second lithium supplement material is consistent with the preparation process of the first lithium supplement material. According to the specific components of the second lithium supplement material, a precursor of the second lithium supplement material is provided, and specific sintering conditions are set.
[0115] In some embodiments, the method for preparing the composite lithium supplement material further comprises the following steps:
[0116] Step S30, crushing the composite lithium supplement material obtained in step S20.
[0117] Specifically, the pulverizing treatment includes processing at a rotation speed of 1000 rpm to 1500 rpm for 1 hour to 1.5 hours.
[0118] As an example, a mechanical rotary crusher may be used for the comminution process.
[0119] The pulverization of the composite lithium supplement material is more conducive to the uniform mixing of the composite lithium supplement material with other materials in the positive electrode material, such as the uniform mixing of the composite lithium supplement material with the positive electrode active material, the conductive agent and other components, so that the composite lithium supplement material can better exert its lithium supplement performance.
[0120] In some embodiments, the preparation method of the composite lithium supplement material can also be prepared by the following method, which specifically includes the following steps:
[0121] Step T10, providing first lithium supplement material particles, second lithium supplement material particles and functional material particles;
[0122] Step T20: mixing the first lithium supplement material particles, the second lithium supplement particles and the functional material particles, and sintering them to obtain a composite lithium supplement material.
[0123] In step T10, the first lithium supplement material particles, the second lithium supplement material particles and the functional material particles are the same as those described above, and will not be described again for the sake of space saving.
[0124] In step T20, since the particle sizes of the first lithium supplement material particles and the second lithium supplement material particles are relatively large and the particle size of the functional material is relatively small, during the sintering process, gaps are formed between adjacent primary particles of the lithium supplement material, and the gaps in the secondary particles are filled with the functional material, making the particles of the lithium supplement material more densely stacked, thereby allowing the two lithium supplement materials to form a more stable structure and maintain the integrity of the structure.
[0125] In step T20, the sintering treatment conditions include: heat treatment at 800°C-900°C for 4h-6h under a protective atmosphere with a heating rate of 3-5°C / min.
[0126] Before the sintering treatment, the first lithium supplement material particles, the second lithium supplement material particles and the functional material particles are degassed and mixed at 1500 rpm to 2500 rpm for 5 min to 10 min.
[0127] As an example, the protective atmosphere includes but is not limited to argon, nitrogen, etc., and the flow rate of the protective atmosphere can be 300-500 mL / min.
[0128] As an example, step T20 can be: degassing and mixing the first lithium replenishing material particles, the second lithium replenishing particles and the functional material particles at 2000rpm for 5 minutes, and then heat treating them at 850℃ for 5 hours at a heating rate of 5℃ / min in an argon atmosphere with a flow rate of 400mL / min, and finally cooling them to room temperature.
[0129] In some embodiments, the composite lithium supplement material further includes ion conductor nanosheets and electron conductor nanosheets, and the preparation method of the composite lithium supplement material is as follows:
[0130] Step A10, arranging an ion conductor nanosheet on a first glass substrate, and forming a first lithium supplement material on the surface of the ion conductor nanosheet to obtain a first composite material;
[0131] Step A20, placing an electronic conductor nanosheet on the second glass substrate, and forming a lithium supplementing material on the surface of the electronic conductor nanosheet to obtain a second composite material;
[0132] Step A30, separating the first composite material from the first glass substrate, covering the first lithium-supplementing material on the surface of the second lithium-supplementing material away from the second glass substrate, depositing at least one of an ion conductor material, an electronic conductor material and a catalyst between the first lithium-supplementing material and the second lithium-supplementing material to form a functional material, and then removing the second glass substrate to obtain a composite lithium-supplementing material; or, separating the second composite material from the second glass substrate, covering the second lithium-supplementing material on the surface of the first lithium-supplementing material away from the first glass substrate, depositing at least one of an ion conductor material, an electronic conductor material and a catalyst between the first lithium-supplementing material and the second lithium-supplementing material to form a functional material, and then removing the first glass substrate to obtain a composite lithium-supplementing material; or, separating the first composite material from the first glass substrate, separating the second composite material from the second glass substrate, covering the second lithium-supplementing material on the surface of the first lithium-supplementing material, depositing at least one of an ion conductor material, an electronic conductor material and a catalyst between the first lithium-supplementing material and the second lithium-supplementing material to form a functional material, and then removing the second glass substrate to obtain a composite lithium-supplementing material.
[0133] In some embodiments, in step A10, the specific process of disposing the ion conductor nanosheet on the first glass substrate is as follows:
[0134] A first glass substrate with a groove is provided, raw materials for preparing ion conductor nanosheets are placed in the groove of the first glass substrate, and a heating treatment is performed, and the ion conductor nanosheets are arranged on the first glass substrate.
[0135] Specific conditions for the heat treatment are set according to the specific components of the ion conductor nanosheets.
[0136] As an example, the specific process of growing lithium aluminum titanium phosphate nanosheets on the first glass substrate is as follows:
[0137] A first glass substrate with a groove is provided, lithium carbonate, aluminum phosphate, ammonium hydrogen phosphate and titanium dioxide are fully mixed, placed in the groove of the first glass substrate, heat treated at 500°C-700°C for 4h-8h, and then sintered at 800°C-1000°C for 2h-10h to obtain lithium aluminum titanium phosphate nanosheets.
[0138] In some embodiments, in step A10, the specific process of forming the first lithium supplement material on the surface of the ion conductor nanosheet is as follows:
[0139] The precursor raw material of the first lithium supplement material is placed on the surface of the ion conductor nanostructured material and subjected to sintering treatment to form the first lithium supplement material.
[0140] The specific conditions of the sintering treatment are set according to the specific components of the first lithium supplementing material.
[0141] As an example, the specific process of forming Li6CoO4 material on the surface of ion conductor nanosheets is as follows:
[0142] After degassing and mixing, excess LiOH and CoO powders are placed on the surface of the ion conductor nanosheets;
[0143] The mixture was kept at 450°C-480°C for 2 hours, then heated to 750°C and sintered for 6 hours to form Li6CoO4 material.
[0144] At 450°C-480°C, LiOH melts and becomes liquid, thereby being evenly distributed on the surface of the ion conductor nanosheet. At this time, a lithium replenishment layer of appropriate thickness can be formed by controlling the mass of the first lithium replenishment material precursor.
[0145] In some embodiments, in step A20, the specific process of disposing the electronic conductor nanosheet on the second glass substrate is as follows:
[0146] The electronic conductor nanosheets of corresponding thickness can be deposited by magnetron sputtering, or can be formed by chemical vapor deposition.
[0147] As an example, metal electronic conductor nanosheets, such as silver nanosheets and aluminum nanosheets, can be obtained by magnetron sputtering.
[0148] As an example, carbon material electronic conductor nanosheets, such as graphene nanosheets, can be obtained by chemical vapor deposition.
[0149] In some embodiments, in step A20, the specific process of forming the second lithium supplementing material on the surface of the electronic conductor nanosheet is as follows:
[0150] The precursor raw material of the second lithium supplement material is placed on the surface of the electronic conductor nanoparticles and subjected to sintering treatment to form the second lithium supplement material.
[0151] According to the specific components of the lithium-supplementing material, the specific conditions of the sintering treatment are set.
[0152] In some embodiments, in step A30, before the first composite material is separated from the first glass substrate or the second composite material is separated from the second glass substrate, the first lithium supplement material and the second lithium supplement material are further subjected to hydroxylation treatment:
[0153] The first lithium replenishing material is treated so that hydroxyl groups are formed on the surface of the first lithium replenishing material away from the ion conductor nanosheet. This process can be prepared by methods well known in the art, such as water etching.
[0154] Exemplarily, the hydroxylation treatment of the first composite material comprises the following steps:
[0155] The first composite material is placed in an ALD deposition device, evacuated to 0.1 torr, and then mixed water vapor is introduced, so that hydroxyl groups are combined on the surface of the first lithium supplementing material.
[0156] The depth of water etching is controlled by controlling the introduction time of mixed water vapor, wherein the mixed water vapor is obtained by mixing water vapor and nitrogen, and the content of water vapor is 0.1ppm to 10ppm. As an example, water vapor is introduced through nitrogen at a flow rate of 50ml / min to 500ml / min.
[0157] In a specific embodiment, the treatment time of the mixed water vapor is related to the mass of the lithium supplementing material and can be 6 s / g to 60 s / g.
[0158] The second lithium supplement material is processed so that hydroxyl groups are formed on the side of the second lithium supplement material away from the electronic conductor nanosheet. This process can be prepared by methods well known in the art, such as water etching.
[0159] The hydroxylation process of the second composite material is the same as the hydroxylation process of the first composite material.
[0160] By hydroxylating the first lithium-supplementing material and the second lithium-supplementing material, hydroxyl groups can be introduced on the surface of the first lithium-supplementing material and the second lithium-supplementing material. These hydroxyl groups are helpful in forming functional materials between the first lithium-supplementing material and the second lithium-supplementing material, especially in forming functional materials by atomic deposition method. Specifically, on the one hand, these hydroxyl groups can form strong chemical bonds with the precursors in the atomic deposition process, thereby enhancing the adhesion between the functional materials and the lithium-supplementing materials; on the other hand, hydroxylation can increase the surface activity of the lithium-supplementing material, making it easier for the atomic deposition precursors to chemically adsorb and react on the surface, which is helpful in forming uniform and dense functional materials. Therefore, hydroxylation treatment can obtain uniformly deposited and dense functional materials.
[0161] In some embodiments, in step A30, the following steps may be used to perform demolding to remove the glass substrate:
[0162] The glass substrate is removed by slight chemical etching, such as heating with an alkali solution having a concentration of less than 0.1 mol / L.
[0163] In some embodiments, in step A30, an atomic deposition method may be used to form a functional material between the first lithium supplementing material and the second lithium supplementing material. The specific process is as follows:
[0164] Place the hydroxylated precursor material in the ALD chamber, evacuate the chamber, monitor the reaction product with mass spectrometry, heat to 150°C, and perform deposition according to conventional deposition steps. Repeat the cycle many times until the mass spectrometry shows that the ALD precursor no longer produces the target product, indicating that the reaction is complete. Cool down, take out, and store in a glove box.
[0165] In some embodiments, the composite lithium supplement material further includes ion conductor nanosheets and electron conductor nanosheets. The composite lithium supplement material can also be prepared by the following method, which specifically includes the following steps:
[0166] Step A'10, placing an ion conductor nanosheet on a first glass substrate, separating the first glass substrate to obtain the ion conductor nanosheet, and forming a first lithium supplement material on the surface of the ion conductor nanosheet to obtain a first composite material;
[0167] Step A'20, placing an electronic conductor nanosheet on a second glass substrate, separating the electronic conductor nanosheet from the second glass substrate, and forming a lithium supplementing material on the surface of the electronic conductor nanosheet to obtain a second composite material;
[0168] Step A'30, covering the first lithium supplement material on the surface of the second lithium supplement material away from the electron nanosheet, depositing at least one of an ion conductor material, an electronic conductor material and a catalyst between the first lithium supplement material and the second lithium supplement material to form a functional material, and obtaining a composite lithium supplement material.
[0169] In step A'10, an ion conductor nanosheet is disposed on the first glass substrate, and a first lithium supplement material is formed on the ion conductor nanosheet. This is consistent with what is described above, and will not be described again to save space.
[0170] In step A'20, an electronic conductor nanosheet is disposed on the second glass substrate, and a second lithium supplementing material is formed on the electronic conductor nanosheet. This is consistent with what is described above, and will not be described again to save space.
[0171] In step A'30, the first lithium supplementing material covers the surface of the second lithium supplementing material and is away from the electronic nanosheet, and at least one of an ion conductor material, an electronic conductor material and a catalyst is deposited between the first lithium supplementing material and the second lithium supplementing material to form a functional material. This is consistent with what is shown above, and will not be described again here to save space.
[0172] Before depositing the functional material, the first lithium replenishing material and the second lithium replenishing material need to be hydroxylated, which is the same as described above and will not be described again to save space.
[0173] In addition, the preparation method of the composite lithium supplement material provided in the embodiments of the present application is described below with reference to the accompanying drawings as appropriate.
[0174] See also Figure 2 , an ion conductive layer 40 is stacked on the surface of the first glass substrate 200, and an I precursor 21 and a II precursor 22 are deposited on the surface of the ion conductive layer 40. The specific formation process is: an ion conductive nanosheet is grown on the surface of the first glass substrate 200, and the ion conductive nanosheet forms an ion conductive layer 40 stacked on the surface of the first glass substrate 200, and an I precursor and a II precursor are deposited on the surface of the ion conductive layer 40. It should be noted that the I precursor 21 and the II precursor 22 are sintered to form a first lithium replenishing layer 20 including a first lithium replenishing material, that is, the first lithium replenishing layer 20 is composed of the first lithium replenishing material, and the first lithium replenishing material is formed by sintering the I precursor 21 and the II precursor 22. Exemplarily, the first lithium replenishing material is Li6CoO4, then the I precursor is LiOH, and the II precursor is CoO.
[0175] See also Figure 3 , the surface of the first glass substrate 200 is stacked with an ion conductive layer 40 and a first lithium supplement layer 20. The intermediate 300 includes a second lithium supplement layer 30 and an electron conductive layer 50 stacked, and the side of the intermediate 300 close to the second lithium supplement layer 30 is covered on the surface of the first lithium supplement layer 20, and there is a gap layer 11 between the first lithium supplement layer 20 and the second lithium supplement layer 30. The specific formation process is: the second composite material is demoulded, and the second glass substrate is removed, and the intermediate 300 is formed at this time; the side of the intermediate 300 close to the second lithium supplement layer 30 is covered on the surface of the first lithium supplement layer 20, because the second lithium supplement layer 30 is not in close contact with the first lithium supplement layer 10, there is a gap layer 11 between the second lithium supplement layer 30 and the first lithium supplement layer 10, and the gap layer 11 is used to deposit functional materials to form the functional material layer 10.
[0176] A third aspect of the embodiments of the present application provides a positive electrode material, including the composite lithium-replenishing material of the present application and / or a composite lithium-replenishing material prepared by the preparation method of the composite lithium-replenishing material of the present application.
[0177] The positive electrode material provided in the third aspect of the embodiment of the present application contains the composite lithium replenishing material of the present application, and the composite lithium replenishing material can delithium at a low delithiation voltage, has good structural stability, and has a high lithium replenishing capacity. It can replenish the lithium ions consumed by the SEI film during the first charge and discharge, thereby achieving efficient lithium replenishment, which is beneficial to improving the first cycle efficiency and reversible capacity of the manufactured lithium-ion battery.
[0178] A fourth aspect of an embodiment of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes the positive electrode material of the present application; the electrolyte can be an electrolyte solution, in which case the secondary battery also includes a diaphragm arranged between the positive electrode plate and the negative electrode plate; or, the electrolyte can be a solid electrolyte solution, in which case the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0179] The secondary battery provided in the fourth aspect of the embodiment of the present application contains the positive electrode material of the present application. Therefore, the secondary battery of the present application has high energy density and cycle performance, and has stable electrochemical performance and high safety performance.
[0180] In some embodiments, the secondary battery of the present application may include a battery cell, a battery module or a battery pack. Among them, a battery cell refers to a battery housing and a battery encapsulated in the battery housing, which is assembled into a bare battery cell including the positive electrode sheet, the negative electrode sheet and other necessary components. A battery module refers to a battery assembled from multiple lithium-ion battery cells. A battery pack refers to a battery assembled from multiple battery modules.
[0181] Since the battery cell, battery module or battery pack contains the composite lithium supplement material of the above-mentioned embodiment of the application, the battery cell, battery module or battery pack has high energy density, good cycle performance, good stability and high safety.
[0182] In some embodiments, the positive electrode plate includes a positive current collector and a positive active layer bonded to at least one surface of the positive current collector, and the positive active layer includes the composite lithium replenishing material of the present application and / or the composite lithium replenishing material prepared by the preparation method of the composite lithium replenishing material of the present application.
[0183] The mass content of the above composite lithium supplementing material contained in the positive electrode active layer may be 0.01 wt % to 95 wt %.
[0184] The positive electrode active layer includes, in addition to the composite lithium supplement material, a binder and a conductive agent, wherein the binder can be a commonly used electrode binder, such as one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives. The conductive agent can be a commonly used conductive agent, such as one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.
[0185] In some embodiments, the positive electrode current collector includes but is not limited to at least one of aluminum foil, carbon-coated aluminum foil, iron foil, tin foil, zinc foil, nickel foil, titanium foil, and manganese foil.
[0186] In some embodiments, the positive electrode material includes a positive electrode active material, a conductive agent and a binder, that is, the composite lithium supplement material of the present application is directly used as a positive electrode active material, and is compounded with a conductive agent and a binder to prepare a positive electrode sheet.
[0187] The preparation process of the positive electrode plate can be: mixing the positive electrode active material, the conductive agent and the binder to obtain an electrode slurry, coating the electrode slurry on the positive electrode collector, and preparing the positive electrode plate through steps such as drying, rolling, and die cutting, wherein the positive electrode active material includes the composite lithium supplement material of the present application.
[0188] In some other embodiments, the positive electrode material includes a positive electrode active material, a lithium supplement agent, a conductive agent and a binder, that is, the composite lithium supplement material of the present application is used as a lithium supplement agent, and is compounded with the positive electrode active material, the conductive agent and the binder to prepare the positive electrode. The positive electrode active material includes but is not limited to lithium iron phosphate, lithium iron manganese phosphate, a ternary positive electrode material (such as NCM ternary or NCA ternary), a binary positive electrode material or a lithium supplement positive electrode material.
[0189] The preparation process of the positive electrode plate can be: mixing the positive electrode active material, the conductive agent, the binder and the lithium supplement agent to obtain an electrode slurry, coating the electrode slurry on the positive electrode collector, and preparing the positive electrode plate through steps such as drying, rolling, and die cutting, wherein the lithium supplement agent includes the composite lithium supplement material of the present application.
[0190] The following uses a number of specific embodiments to illustrate the composite lithium supplement material and its preparation method and application in the embodiments of the present application.
[0191] Composite lithium supplement material and preparation method thereof embodiment:
[0192] Example 1
[0193] This embodiment provides a composite lithium supplement material, including a functional material (Co3O4), a first lithium supplement material (Li6CoO4) and a second lithium supplement material (Li2NiO2), wherein the functional material is filled between the first lithium supplement material and the second lithium supplement material. The mass ratio of the first lithium supplement material, the second lithium supplement material and the functional material is 45:45:10.
[0194] A method for preparing a composite lithium supplement material comprises the following steps:
[0195] Step 1: Prepare the first lithium supplement material and the second lithium supplement material
[0196] The preparation process of the first lithium supplement material is as follows: LiOH and CoO with a mass ratio of 6:1 are placed on the surface of a glass substrate, kept at 450°C for 2 hours, then heated to 750°C and sintered for 6 hours to form Li6CoO4 on the surface of the glass substrate, and then treated with 0.05 mol / L sodium hydroxide solution to separate from the glass substrate to obtain the first lithium supplement material.
[0197] The preparation process of the second lithium-supplementing material is as follows: LiOH and NiO with a mass ratio of 3:1 are placed on the surface of a glass substrate, kept warm at 450°C for 2 hours, then heated to 750°C and sintered for 6 hours to form Li2NiO2 material on the surface of the glass substrate, and then treated with 0.05 mol / L sodium hydroxide solution to separate from the glass substrate, which is the second lithium-supplementing material.
[0198] Step 2: Hydroxylation
[0199] The first lithium supplement material is placed in an ALD chamber, evacuated to 0.1 torr, and then mixed water vapor is introduced for etching, so that the surface of the first lithium supplement material is combined with hydroxyl groups. The introduction time is 20 seconds, wherein the mixed water vapor includes nitrogen and water vapor, and the content of water vapor is 1ppm; the flow rate of the mixed water vapor is 100ml / min;
[0200] The second lithium replenishing material is placed in an ALD chamber, evacuated to 0.1 torr, and then mixed water vapor is introduced for etching so that hydroxyl groups are bound to the surface of the second lithium replenishing material. The introduction time is 20 seconds, wherein the mixed water vapor includes nitrogen and water vapor, and the water vapor content is 1 ppm; the flow rate of the mixed water vapor is 100 ml / min.
[0201] Step 3: Forming functional materials
[0202] A second lithium-replenishing material having a hydroxyl group on its surface is placed on the surface of the first lithium-replenishing material, placed in an ALD chamber, evacuated to 0.1 torr, introduced 1 torr Co(CP)2, reacted for 5 minutes, purged with nitrogen for 30 minutes, then introduced ozone for 6 minutes, reacted for 5 minutes, and purged with nitrogen for 30 minutes. This is one cycle, and the reaction is continuously cyclically performed until the pressure in the chamber does not change when Co(CP)2 is introduced in the next cycle, and the reaction is terminated. Co3O4 is grown between the first lithium-replenishing material and the second lithium-replenishing material to obtain a primary composite lithium-replenishing material.
[0203] Step 4: Crushing
[0204] The primary composite lithium supplement material obtained in step 3 is placed in a mechanical rotary crusher and crushed at a rotation speed of 1200 r / min for 1 hour to obtain a composite lithium supplement material.
[0205] Example 2
[0206] This embodiment provides a composite lithium supplement material, which is different from the first embodiment in that the functional material is an ion conductor material lithium aluminum titanium phosphate, and the rest is the same as the first embodiment.
[0207] Example 3
[0208] This embodiment provides a composite lithium supplement material, which is different from the embodiment 1 in that the functional material is the electronic conductor material graphene, and the rest is the same as the embodiment 1.
[0209] Example 4
[0210] This embodiment provides a composite lithium supplement material, which is different from the embodiment 1 in that it also includes an ion conductor nanosheet (lithium aluminum titanium phosphate). Specifically, the composite lithium supplement material includes an ion conduction layer, a first lithium supplement layer (Li6CoO4), a functional material layer (Co3O4) and a second lithium supplement layer (Li2NiO2) stacked from bottom to top, and the ion conduction layer is formed by the ion conductor nanosheet. The thickness of the functional material layer is 400nm, the thickness of the first lithium supplement layer is 2000nm, the thickness of the second lithium supplement layer is 2000nm, and the thickness of the ion conduction layer is 400nm.
[0211] A method for preparing a composite lithium supplement material comprises the following steps:
[0212] Step 1: Preparation of ion conductor nanosheets
[0213] The raw material components of lithium carbonate, aluminum phosphate, ammonium hydrogen phosphate, and titanium dioxide are fully mixed in a mass ratio of 3:1:3:3, placed in the groove of the first glass substrate, and heat treated at 600°C for 4 hours to melt the raw material components and flatten the groove. They are then sintered at 900°C for 5 hours to form lithium aluminum titanium phosphate, and then treated with 0.05 mol / L sodium hydroxide solution to separate from the glass substrate to obtain ion conductor nanosheets.
[0214] Step 2: Preparation of the first lithium supplementation layer
[0215] After degassing and mixing LiOH and CoO powders in a mass ratio of 6:1, they are placed on the surface of ion conductor nanosheets, kept at 450°C for 2 hours, and then heated to 750°C and sintered for 6 hours to form Li6CoO4 material on the surface of the ion conductor nanosheets to obtain the first lithium replenishment layer.
[0216] Step 3: Preparation of the second lithium supplementation layer
[0217] LiOH and NiO with a mass ratio of 3:1 are placed on the surface of a glass substrate, kept at 450°C for 2 hours, and then heated to 750°C and sintered for 6 hours to form Li2NiO2 material on the surface of the glass substrate. It is then treated with 0.05 mol / L sodium hydroxide solution to separate from the glass substrate to obtain a second lithium replenishment layer.
[0218] Step 4: Hydroxylation
[0219] The first lithium replenishing layer and the second lithium replenishing layer loaded on the ion conductor nanosheet obtained in step 2 are placed in the ALD chamber respectively, evacuated to 0.1 torr, and then mixed water vapor is introduced for etching, so that the surfaces of the first lithium replenishing material and the second lithium replenishing material are both combined with hydroxyl groups. The introduction time is 20 seconds, wherein the mixed water vapor includes nitrogen and water vapor, and the water vapor content is 1ppm; the flow rate of the mixed water vapor is 100ml / min.
[0220] Step 5: Forming a functional material layer
[0221] A second lithium-replenishing material having a hydroxyl group on its surface is placed on the surface of the first lithium-replenishing material, placed in an ALD chamber, evacuated to 0.1 torr, introduced 1 torr Co(CP)2, reacted for 5 minutes, purged with nitrogen for 30 minutes, then introduced ozone for 6 minutes, reacted for 5 minutes, and purged with nitrogen for 30 minutes. This is one cycle, and the reaction is continuously cyclically performed until the pressure in the chamber does not change when Co(CP)2 is introduced in the next cycle, and the reaction is terminated. A functional material layer is grown between the first lithium-replenishing material and the second lithium-replenishing material to obtain a primary composite lithium-replenishing material.
[0222] Step 6: Crushing
[0223] The primary composite lithium supplement material obtained in step 5 is placed in a mechanical rotary crusher and crushed at a rotation speed of 1200 r / min for 1 hour to obtain a composite lithium supplement material.
[0224] Example 5
[0225] This embodiment provides a composite lithium supplement material, which is different from the embodiment 1 in that it also includes an electronic conductor nanosheet (graphene). Specifically, the composite lithium supplement material includes a first lithium supplement layer (Li6CoO4), a functional material layer (Co3O4), a second lithium supplement layer (Li2NiO2) and an electronic conduction layer stacked from bottom to top, and the electronic conduction layer is formed by the electronic conductor nanosheet. The thickness of the functional material layer is 400nm, the thickness of the first lithium supplement layer is 2000nm, the thickness of the second lithium supplement layer is 2000nm, and the thickness of the electronic conduction layer is 400nm.
[0226] A method for preparing a composite lithium supplement material comprises the following steps:
[0227] Step 1: Forming the first lithium replenishment layer
[0228] LiOH and CoO with a mass ratio of 6:1 are placed on the surface of a glass substrate, kept at 450°C for 2 hours, then raised to 750°C and sintered for 6 hours to form Li6CoO4 on the surface of the glass substrate. It is then treated with 0.05 mol / L sodium hydroxide solution to separate from the glass substrate, forming the first lithium replenishment layer.
[0229] Step 2: Preparation of electronic conductor nanosheets
[0230] Using ethylene as a carbon source, a chemical vapor deposition method is used at 800°C to form graphene sheets on the surface of a glass substrate, and then treated with a 0.05 mol / L sodium hydroxide solution to separate from the glass substrate, thus forming an electronic conductor nanosheet.
[0231] LiOH and NiO with a mass ratio of 3:1 are placed on the surface of the electronic conductor nanosheet, kept at 450°C for 2 hours, and then heated to 750°C and sintered for 6 hours to form Li2NiO2 material, i.e. the second lithium replenishment layer, on the surface of the electronic conductor nanosheet.
[0232] Step 3: Hydroxylation
[0233] The second lithium replenishing layer and the first lithium replenishing layer loaded on the electronic conductor nanosheet obtained in step 2 are placed in the ALD chamber respectively, evacuated to 0.1 torr, and then mixed water vapor is introduced for etching, so that the surfaces of the first lithium replenishing material and the second lithium replenishing material are both bound with hydroxyl groups. The introduction time is 20 seconds, wherein the mixed water vapor includes nitrogen and water vapor, and the water vapor content is 1 ppm; the flow rate of the mixed water vapor is 100 ml / min.
[0234] Step 4: Forming a functional material layer
[0235] A first lithium-replenishing material having a hydroxyl group on its surface is placed on the surface of a second lithium-replenishing material, placed in an ALD chamber, evacuated to 0.1 torr, introduced 1 torr Co(CP)2, reacted for 5 minutes, purged with nitrogen for 30 minutes, then introduced ozone for 6 minutes, reacted for 5 minutes, and purged with nitrogen for 30 minutes. This is one cycle, and the reaction is continuously cyclically performed until the pressure in the chamber does not change when Co(CP)2 is introduced in the next cycle, and the reaction is terminated. A functional material layer is grown between the first lithium-replenishing material and the second lithium-replenishing material to obtain a primary composite lithium-replenishing material.
[0236] Step 5: Crushing
[0237] The primary composite lithium supplement material obtained in step 4 is placed in a mechanical rotary crusher and crushed at a rotation speed of 1200 r / min for 1 hour to obtain a composite lithium supplement material.
[0238] Example 6
[0239] This embodiment provides a composite lithium supplement material, which is different from the embodiment 1 in that it also includes an ion conductor nanosheet (lithium aluminum titanium phosphate) and an electronic conductor nanosheet (graphene). Specifically, the composite lithium supplement material includes an ion conduction layer, a first lithium supplement layer (Li6CoO4), a functional material layer (Co3O4), a second lithium supplement layer (Li2NiO2) and an electronic conduction layer stacked from bottom to top, the ion conduction layer is formed by the ion conductor nanosheet, and the electronic conduction layer is formed by the electronic conductor nanosheet. The thickness of the functional material layer is 400nm, the thickness of the first lithium supplement layer is 2000nm, the thickness of the second lithium supplement layer is 2000nm, the thickness of the ion conduction layer is 400nm, and the thickness of the electronic conduction layer is 400nm.
[0240] A method for preparing a composite lithium supplement material comprises the following steps:
[0241] Step 1: Preparation of ion conductor nanosheets
[0242] The raw material components of lithium carbonate, aluminum phosphate, ammonium hydrogen phosphate, and titanium dioxide are fully mixed in a mass ratio of 3:1:3:3, placed in the groove of the first glass substrate, and heat treated at 600°C for 4 hours to melt the raw material components and flatten the groove. They are then sintered at 900°C for 5 hours to form lithium aluminum titanium phosphate, and then treated with 0.05 mol / L sodium hydroxide solution to separate from the glass substrate to obtain ion conductor nanosheets.
[0243] Step 2: Preparation of the first lithium supplementation layer
[0244] After degassing and mixing LiOH and CoO powders in a mass ratio of 6:1, they are placed on the surface of ion conductor nanosheets, kept at 450°C for 2 hours, and then heated to 750°C and sintered for 6 hours to form Li6CoO4 material on the surface of the ion conductor nanosheets to obtain the first lithium replenishment layer.
[0245] Step 3: Preparation of electronic conductor nanosheets
[0246] Using ethylene as a carbon source, a chemical vapor method is used at 800°C to deposit graphene sheets on the surface of a glass substrate, and then they are treated with a 0.05 mol / L sodium hydroxide solution to separate from the glass substrate, thus forming an electronic conductor nanosheet.
[0247] Step 4: Preparation of the second lithium supplementation layer
[0248] LiOH and NiO with a mass ratio of 3:1 are placed on the surface of the electronic conductor nanosheet, kept at 450°C for 2 hours, and then heated to 750°C and sintered for 6 hours to form Li2NiO2 material, i.e. the second lithium replenishment layer, on the surface of the electronic conductor nanosheet.
[0249] Step 5: Hydroxylation
[0250] The first lithium replenishing layer loaded on the ion conductor nanosheet obtained in step 2 and the second lithium replenishing layer loaded on the electronic conductor nanosheet obtained in step 4 are placed in the ALD chamber respectively, evacuated to 0.1 torr, and then mixed water vapor is introduced for etching, so that the surfaces of the first lithium replenishing material and the second lithium replenishing material are both combined with hydroxyl groups. The introduction time is 20 seconds, wherein the mixed water vapor includes nitrogen and water vapor, and the water vapor content is 1ppm; the flow rate of the mixed water vapor is 100ml / min.
[0251] Step 6: Prepare functional material layer
[0252] A second lithium-replenishing material having a hydroxyl group on its surface is placed on the surface of the first lithium-replenishing material, placed in an ALD chamber, evacuated to 0.1 torr, introduced 1 torr Co(CP)2, reacted for 5 minutes, purged with nitrogen for 30 minutes, then introduced ozone for 6 minutes, reacted for 5 minutes, and purged with nitrogen for 30 minutes. This is one cycle, and the reaction is continuously cyclically performed until the pressure in the chamber does not change when Co(CP)2 is introduced in the next cycle, and the reaction is terminated. A functional material layer is grown between the first lithium-replenishing material and the second lithium-replenishing material to obtain a primary composite lithium-replenishing material.
[0253] Step 7: Crushing
[0254] The primary composite lithium supplement material obtained in step 6 is placed in a mechanical rotary crusher and crushed at a rotation speed of 1200 r / min for 1 hour to obtain a composite lithium supplement material.
[0255] Example 7
[0256] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the content of the lithium supplement material is different. Specifically, the thickness of the first lithium supplement layer is 400 nm, and the thickness of the second lithium supplement layer is 400 nm.
[0257] Example 8
[0258] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the content of the lithium supplement material is different. Specifically, the thickness of the first lithium supplement layer is 3000 nm, and the thickness of the second lithium supplement layer is 3000 nm.
[0259] Example 9
[0260] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the content of the functional material layer is different. Specifically, the thickness of the functional material layer is 50 nm.
[0261] Example 10
[0262] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the content of the functional material layer is different. Specifically, the thickness of the functional material layer is 800 nm.
[0263] Embodiment 11
[0264] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the material of the functional material layer is different. Specifically, the material of the functional material layer is manganese oxide.
[0265] Example 12
[0266] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the material of the functional material layer is different. Specifically, the material of the functional material layer is the ion conductor material lithium lanthanum titanate.
[0267] Example 13
[0268] This embodiment provides a composite lithium supplement material, which is different from Embodiment 6 in that the material of the functional material layer is different. Specifically, the material of the functional material layer is the electronic conductor material Al.
[0269] Comparative Example 1
[0270] This comparative example provides a composite lithium supplement material, which only includes Li6CoO4 and Li2NiO2.
[0271] Comparative Example 2
[0272] This comparative example provides a composite lithium supplement material, which is different from Example 1 in that Li6CoO4 and Li2NiO2 are mixed and distributed on one surface of the functional material layer (Co3O4).
[0273] Lithium-ion battery example:
[0274] The composite lithium supplement materials provided in the above-mentioned Examples 1 to 13 and the composite lithium supplement materials provided in Comparative Examples 1 to 2 are respectively assembled into positive electrodes and lithium-ion batteries according to the following methods:
[0275] Positive electrode: Under the same conditions, the composite lithium supplement material: SP (conductive carbon black): PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 90:4:6, and N-methylpyrrolidone (NMP) is used as a solvent to mix the materials evenly to form a slurry, which is then evenly coated on the surface of the aluminum foil, rolled to a certain thickness, and vacuum dried at 110°C for 12 hours to form a positive electrode sheet; wherein the composite lithium supplement material is the composite lithium supplement material provided in the above-mentioned Examples 1 to 12 and the composite lithium supplement material provided in the comparative example.
[0276] Counter electrode: Lithium metal sheet.
[0277] Electrolyte: The electrolyte is a 1 mol / L LiPF6 / ethylene carbonate:ethyl methyl carbonate (volume ratio) = 1:1 solution.
[0278] Diaphragm: Polypropylene microporous membrane.
[0279] Lithium-ion battery assembly: The lithium metal sheet-diaphragm-electrolyte-positive electrode sheet is assembled into a button-type lithium-ion battery in an inert atmosphere glove box. The batteries containing the composite lithium supplement materials provided in Examples 1 to 13 are respectively recorded as Examples S1 to S13, and the batteries containing the lithium supplement materials provided in Comparative Examples 1 to 2 are recorded as Comparative Examples DS1 to DS2.
[0280] Performance Testing
[0281] (1) Electronic conductivity test
[0282] The resistivity of the lithium supplementing additive in each embodiment and comparative example was calculated by four-probe method testing, and the electronic conductivity was obtained by taking the reciprocal of the resistivity.
[0283] (2) Ionic conductivity test
[0284] The ionic conductivity of the lithium supplement additive in each embodiment and comparative example was calculated by EIS impedance test.
[0285] (3) Electrochemical performance test
[0286] The electrochemical performance of each lithium ion battery assembled in the above lithium ion battery embodiment was tested as shown in Table 1, and the test conditions were as follows:
[0287] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.7V. The battery was charged at a constant voltage of 4.7V. After the charging process was completed, the battery was allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V. The charging platform was observed during the charging process to obtain the delithiation potential of the lithium supplement material.
[0288] The relevant performance test results of the lithium secondary battery are shown in Table 1 below.
[0289] Table 1 Related performance test results
[0290]
[0291] From the test results of Example 1 and Comparative Examples 1 and 2 in Table 1, it can be seen that compounding the lithium supplement material on a single surface of the catalyst is beneficial to reducing the decomposition voltage of the lithium supplement material and improving the decomposition degree of the lithium supplement material, thereby improving the charging capacity and lithium supplement capacity of the lithium supplement material. However, when the two lithium supplement materials are evenly distributed on both sides of the catalyst layer, the decomposition voltage of the lithium supplement material can be more significantly reduced, thereby improving the charging capacity and lithium supplement capacity of the lithium supplement material to a greater extent.
[0292] It can be seen from the test results of Examples 1 to 3 in Table 1 that there is a certain relationship between the performance of the composite lithium supplement material and the properties of the functional material. For example, when the functional material in Example 2 is an ion conductor material, the ion conductivity of the composite lithium supplement material can be greatly improved. When the functional material in Example 3 is an electronic conductor material, the electronic conductivity of the composite lithium supplement material can be greatly improved. The improvement of ionic conductivity or electronic conductivity will slightly reduce the decomposition voltage of the lithium supplement material, thereby correspondingly improving the charging capacity and lithium supplement capacity.
[0293] From the test results of Example 1, Example 4, Example 5 and Example 6 in Table 1, it can be seen that when the functional material is a catalyst, the decomposition voltage of the lithium supplement material will be reduced. When both sides are single conductive materials, the single conductivity of the composite material will be correspondingly improved, such as Example 4 and Example 5; and when there are corresponding conductive materials on both sides, the ionic conductivity and electronic conductivity of the composite lithium supplement material can be improved at the same time, such as Example 6. This synergistic effect can further reduce the decomposition voltage of the lithium supplement material, and the composite lithium supplement material also has the best charging capacity and lithium supplement capacity.
[0294] It can be seen from the test results of Example 6, Example 7 and Example 8 in Table 1 that when the content of the lithium supplement material is too little or too much relative to the content of other functional materials, the lithium supplement performance of the composite material will be affected. When the content is too little, although the ionic conductivity and electronic conductivity of the composite lithium supplement material will be improved and the decomposition voltage will be reduced, the proportion of the lithium supplement material is small, resulting in too low charging capacity and lithium supplement capacity of the lithium supplement material; when the content is too much, the ionic conductivity and electronic conductivity of the composite lithium supplement material will be directly reduced, and its decomposition voltage will be increased, resulting in a reduction in the charging capacity and lithium supplement capacity of the composite lithium supplement material compared with Example 6.
[0295] It can be seen from the test results of Example 6, Example 9 and Example 10 in Table 1 that when the content of the functional material, that is, the catalyst, is too low or too high, the proportion of the lithium supplement material is correspondingly too high or too low. At this time, the composite lithium supplement material has a similar effect to when the content of the lithium supplement material is too low or too high. Compared with Example 6, the decomposition voltage, electronic conductivity and ion conductivity of the composite lithium supplement material also change accordingly, so that the charging capacity and the lithium supplement capacity are reduced to a certain extent.
[0296] It can be seen from the test results of Example 6, Example 11, Example 12 and Example 13 in Table 1 that the excellent performance of the composite lithium supplement material is the result of the synergistic effect of the structure itself and multiple functional materials, rather than a single material itself. Therefore, when replacing functional materials, such as catalysts, ion conductor materials, and electronic conductors, the decomposition voltage, electronic conductivity, ion conductivity and other properties of the composite lithium supplement material also have corresponding changes.
[0297] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A composite lithium supplement material, characterized in that: include: At least two lithium supplementing materials are provided, and a functional material is filled between the two adjacent lithium supplementing materials, wherein the functional material comprises at least one of an ion conductor material, an electronic conductor material and a catalyst.
2. The composite lithium supplement material according to claim 1, characterized in that: The two lithium supplementing materials and the functional material form a stacked structure, and the functional material forms a functional material layer between the two lithium supplementing materials.
3. The composite lithium supplement material according to claim 2, characterized in that: The two lithium supplementing materials form secondary particles, and the gaps between the secondary particles are filled with the functional material; and / or The functional material layer comprises an atomic deposition layer obtained by depositing at least one of the ion conductor material, the electronic conductor material and the catalyst using an atomic layer deposition technique; and / or The two lithium-replenishing materials include a first lithium-replenishing material and a second lithium-replenishing material. The functional material layer includes a first surface and a second surface that are oppositely arranged along the thickness direction. The first lithium-replenishing material is attached to the first surface of the functional material layer to form a first lithium-replenishing layer. The second lithium-replenishing material is attached to the second surface of the functional material layer to form a second lithium-replenishing layer.
4. The composite lithium supplement material according to claim 2, characterized in that: The two lithium-supplementing materials and the functional material layer form a lithium-supplementing unit, the composite lithium-supplementing material comprises a lithium-supplementing matrix, and the lithium-supplementing matrix comprises at least one of the lithium-supplementing units; The electronic conductor material includes at least one of a carbon material, a metal single atom, an alloy, and a conductive polymer material; and / or The ion conductor material comprises at least one of a metal ion conductor, a ceramic ion conductor, and a solid electrolyte; and / or The catalyst comprises at least one of a transition metal oxide, a transition metal carbide, a transition metal sulfide, and a transition metal phosphide; and / or The thickness of the first lithium replenishing layer is 100nm-3000nm; and / or The thickness of the second lithium replenishing layer is 100nm-3000nm; and / or The thickness of the functional material layer is 20nm-800nm.
5. The composite lithium supplement material according to claim 4, characterized in that: The lithium supplement matrix includes a first surface and a second surface that are arranged opposite to each other along the thickness direction; The composite lithium supplement material further includes an ion conductor nanosheet, and the ion conductor nanosheet is bonded to the first surface of the lithium supplement matrix; and / or The composite lithium supplement material further includes an electronic conductor nanosheet, and the electronic conductor nanosheet is bonded to the second surface of the lithium supplement matrix.
6. The composite lithium supplement material according to claim 5, characterized in that: At least one of the ion conductor nanosheets is stacked on a surface of the lithium-supplementing matrix away from the functional material layer to form an ion conducting layer; and / or At least one of the electronic conductor nanosheets is stacked on a surface of the lithium-supplementing matrix away from the functional material layer to form an electronic conduction layer.
7. The composite lithium supplement material according to claim 6, characterized in that: The thickness of the ion conductor nanosheet is 50nm-800nm; and / or The thickness of the electronic conductor nanosheet is 50nm-800nm; and / or The thickness of the ion conducting layer is 50nm-2000nm; and / or The thickness of the electron conducting layer is 50nm-2000nm; and / or The overall thickness of the composite lithium supplement material is in the range of 300nm-7000nm.
8. A method for preparing a composite lithium supplement material, characterized in that: The following steps are involved: Providing a first lithium supplement material and a second lithium supplement material; At least one of the first lithium supplement material and the second lithium supplement filling ion conductor material, electronic conductor material and catalyst forms a functional material to obtain a composite lithium supplement material.
9. A positive electrode material, characterized in that: The invention comprises the composite lithium-supplementing material according to any one of claims 1 to 7 and / or the composite lithium-supplementing material prepared by the preparation method of the composite lithium-supplementing material according to claim 8.
10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode sheet comprises the positive electrode material as claimed in claim 9.
Citation Information
Cited By
Positive pole piece, preparation method thereof and battery
CN120376570A